MyVitaQus: My vitamin quick search engine booster for IR 4.0 - Rahmah, Mokhtar; Raza, Muhammad Ahsan; Noraziah, Ahmad; Roslina, Abd Hamid; Nor Azhar, Ahmad; Fauziah, Zainuddin; Nurul Saidatul Akmal, Ab. Razak (2018)
MyVitaQus is a powerful semantic search tool to locate documents related to your requirements from the diverse and unstructured big data world.